The 9th girl - Hoag, Tami. (New York, New York : Dutton, 2013)
The ninth unidentified body to turn up in Minneapolis in 2012 is nicknamed Jane Doe 9. When Kovac and Liska take on the case, they discover a shocking fact: This victim has been found without any identifiable characteristics, except for those that peg her as an adolescent girl.
Keywords: Young women -- Crimes against -- Fiction; Murder -- Investigation -- Fiction; Psychological fiction; Mystery fiction; Suspense fiction